The political economy of classical Athens : a naval perspective - O'Halloran, Barry (Trinity College (Dublin, Ireland). Department of Classics, 2017)
This dissertation endeavours to provide an analysis of the political economy of classical Athens from the perspective of the development of its navy. Traditionally, scholarship has viewed the economy of Athens as primitive, founded on subsistence agriculture with little or no economic growth. On the question of the navy, scholarship has also had a consistent and fairly uniform view that Athens' navy was the product of a fortuitous combination of a lucky exceptional silver strike and the foresight and perspicacity of one man, Themistocles. This serendipitous set of circumstances resulted in the creation, virtually from scratch, of a two hundred strong trireme fleet during the last years of the 480s.
Keywords: Classics, Ph.D.; PhD Trinity College Dublin, 2017